Learning Media for Counting Operations Based on Pictoblox Gamification: Development Research in Class 1 Elementary School (Al-Aulad: Journal of Islamic Primary Education, 2023)
This study aims to describe the development of pictoblox gamification learning media for mathematics learning in grade 1 elementary school, describe the design of pictoblox gamification learning media as a problem solution, describe the feasibility and testing of products that have been made, and describe the requirements for the final product of pictoblox gamification-based learning media. . The research used the Design Based Research (DBR) research and development method using the Reeves model research stages, namely: 1) assistance and problem analysis; 2) develop solutions; 3) do the process iteratively 4) reflection. The data collection technique used is through data collection using preliminary studies and field studies. This data collection technique uses several research instruments, in the form of (1) interview instruments conducted by researchers by asking several questions to the teacher; (2) expert judgment, conducted based on the results of validation by experts, where expert validation in this study was carried out to media expert lecturers and elementary school teachers; (3) questionnaires, conducted to teachers and grade I students at the elementary school under study; and (4) documentation in the form of writings, pictures, or monumental works of a person. This documentation is intended to support data regarding the teacher's experience using learning media in the classroom and students' enthusiasm in learning using the media. Based on the results of research at Rajamandala Elementary School, Tasikmalaya Regency, research data was obtained which showed that the pictoblox gamification-based arithmetic operations learning media developed was feasible to use in learning. Feasibility is shown from the results of validation by expert validators, and the usability of the results of trials that have been carried out. So based on the results of this study, the development of pictoblox-based learning media can be used as an alternative media in learning.